Pembuatan Peta Timbul Sebagai Media Pembelajaran Geografi: Making Embossed Maps as Learning Media for Geography - Chandra, Deded; Wilis, Ratna; Frananda, Hendry; Rahmi, Lailatur; Arif, Dian Adhetya; Wijayanto, Bayu; Putra, Aprizon (Pedagogia : Jurnal Pendidikan, 2019)
This article aims to improve the ability of teachers and students to make media maps arise and improve teacher understanding and ability in terms of understanding pedagogical aspects that can be seen from the process of designing a Learning Implementation Plan (LIP) especially in terms of choosing a model or learning method. This activity was held at SMAN 2 using training methods, question and answer, and practice. In accordance with the objectives of the implementation of the activity, it is expected that teachers and students have an increased ability in terms of mastery to make map media arise. Then the teacher can also improve the teacher's understanding/ability in terms of understanding pedagogical aspects that can be seen from the process of designing the LIP especially in terms of choosing a learning model. By carrying out training to improve teacher skills in developing learning media, Geography Teachers are expected to have sufficient competence in terms of designing and utilizing media so that quality learning is created.